Metode Learning by Playing pada Aplikasi Perangkat Lunak Bahasa Inggris Dasar Usia Taman Kanak-Kanak - Handayani, Maya Rini (LP2M of Institute for Research and Community Services - UIN Walisongo, 2016)
Starting in 2016, It is compulsory for every child in Indonesia to learn in kindergarten schoolÂ for 1 year according to the rules of UNESCO. This rule makes a lot of kindergartens providing alternative extra curricular such as Basic English extracurricular to attract parents to educate their children at the school. But unfortunately sometimes the school neglect the quality of school teachers who will teach the English extracurricular. It is make the writer provides an alternative solution for the kindergarten school to make an Basic English application. The created applications is the application of a basic level of English language by using the learning by playing method as an alternative learning. Method of learning by playing is a method of studying subjects for kindergarten children using the game. Therefore, application of Basic English is made using such methods. The benefits of the basic English application using the method of learning by playing are 1) to help teachers who teach basic English to minimize the errors in teaching, 2) to alleviate expenses to recruit new English teachers, and 3) to save the youth Muslim generationâ€™sintelligence from an early age.